Analisis dan Perbaikan Produktivitas Proses Produksi di PT. XYZ - Erikco Limestan; Roki -; Jusra Tampubolon (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2022)
The production process of the company/manufacturing industry still often get obstacles, it made the product specifications produced are not in accordance with the production. However, the company must also evaluate and improve its production process. One of them is PT. XYZ, which is engaged in the production of concrete, namely electric poles and piles. This company produces electric poles with various sizes including 9 meters, 11 meters, 12 meters. This research was conducted to measure the level of productivity and identify problems in the production process of electric poles at PT XYZ. This research used Overall Equipment Effectiveness (OEE) as the methode, which is a calculation carried out to determine the effectiveness of the machine. There are three elements of productivity as well as equipment effectiveness that can be measured by Overall Equipment Effectiveness (OEE), namely availability, performance efficiency, and product quality level. With the Overall Equipment Effectiveness (OEE) method in this study, this research tried to measure the level of effectiveness of the electric pole production process and found the root cause of the problems that hindered the achievement of productivity at PT XYZ.